Influence of light and kairomone baiting systems on trap collections of biting midges in southern Sweden. Issue 1 (3rd June 2020) - Bray, Daniel; Isberg, Elin; Hillbur, Ylva; Ignell, Rickard
ABSTRACT: Effective surveillance is essential for protecting livestock from Culicoides biting midges and the viruses they transmit. The objective of this study was to determine how the baiting system used in traps (UV, incandescent light, incandescent light with CO2, and incandescent light with CO2 and 1‐octen‐3‐ol) influences estimates of midge population abundance, parity, and diel activity. This was achieved through a standardized trapping protocol conducted in three habitats in Sweden. UV light traps caught the most Culicoides species and more C. obsoletus complex females than incandescent light traps. Traps baited with CO2 plus 1‐octen‐3‐ol caught more female C. impunctatus than incandescent light traps. No consistent effect of bait type was found on C. obsoletus parity rate, as estimated from the proportion of midges with presence or absence of pigmentation. Midge activity, as reflected by trap catches, peaked between ‐3 h and +3 h relative to sunset, with UV traps catching significantly more female C. obsoletus complex and C. impunctatus at and after sunset than before sunset. We conclude that baiting system can influence biting midge collections, even using identical traps. Effective surveillance may require more than one bait type and kairomones to attract species that do not feed exclusively on cattle.